Correlation between perceptions with the occurence of dental decay among cruise employee candidates who visited dental clinics in Denpasar year 2012 - Putu Eka Pratiwi; Anak Agung Sagung Sawitri; I Nyoman Adiputra (Universitas Udayana, 2013)
Based on Basic Health Research (Riskesdas) in 2007, the prevalence of dental decay in Bali Province was 22.5%. The proportion of dental decay among the cruise employee candidates who visited a dental clinic was 96.2%. The behavior to prevent decay influences the occurrence of decay, in which perception affects the behavior. This case control study aims to examine the correlations between perception of susceptibility, seriousness, barriers, benefits, trigger factors and knowledge on dental decay with the occurence of dental decay at the cruise employee candidates. The study conducted between June-October 2012. The case in this study was the cruise employee candidates who were diagnosed of having dental decay and the control was them who are not. Risk factors explored include perception of susceptibility, seriousness, barriers, benefits and trigger factors that correlated with dental decay using structured questionaire. Education and age are the control variables. Data were analysed using univariate, bivariate and multivariate. The crude OR indicates that perception of seriousness [OR=4.38; 95%CI: 2.13-8.99], benefits [OR=3.08; 95%CI: 1.51-6.28] and knowledge [OR=4.85; 95%CI: 2.32-10.11] can increase risk of dental decay. The adjusted OR shows that perception of seriousness [OR=10.5; 95%CI: 3.73-29.97], benefits [OR=3.3; 95%CI: 1.41-8.19], barriers [OR=3.3; 95%CI: 1.2-9.35] and knowledge [OR=6.4; 95%CI: 2.59-16.19] increased risk of dental decay. Efforts to improve perception of seriousness, benefit, barrier and knowledge on dental decay for cruise employee candidates need to be conducted in a sustainable manner.